THE EFFECT OF HYPNOBIRTHING RELAXATION ON ANXIETY LEVELS OF TRIMESTER III PREGNANT WOMEN IN DEALING WITH LABOR PREPARATION IN BAYEMAN VILLAGE - Emi Widayanti; Titik Suhartini; Iit Ermawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The unpreparedness of the mother in facing childbirth is one of the causes of the high maternal mortality rate (MMR) and preparation for childbirth includes psychological preparation. To reduce the level of anxiety and fear of pregnant women in the third trimester in the examination, it is very necessary to explain the changes that will occur in themselves, especially the psychological changes they will face. This study was to analyze the effect of hypnobirthing relaxation on the anxiety level of third trimester pregnant women in facing childbirth preparation. This research is a pre-experimental research, while the research design is bivariate analysis. The data was taken from the pregnancy book register in Bayeman Village, Tongas District, which was held from July 13, 2022 to August 3, 2022 with a population of 14 third trimester pregnant women. The sample studied was 14 respondents and taken by Total Sampling. Data collection includes editing, coding, scoring, and tabulating, then the data is analyzed using computerized calculations, namely the SPSS program. Of the 14 respondents studied, most (51.1%) were aged 21-35 years, while the education level of the respondents was mostly (38.4%) elementary school education, the type of work of the respondents were mostly (84.6%) as housewives, the level of anxiety before relaxation hypnobirthing (71.4%) with moderate anxiety level, anxiety level after hypnobirthing relaxation (92.9%) with mild anxiety level and the results of data analysis using SPSS obtained p value = 0.000 and = 0.05 which means Ho is reject and H1 is accepted so that it can be concluded that there is an effect of hypnobirthing relaxation on third trimester pregnant women in facing labor preparation. It is hoped that Bayeman Village can reduce the anxiety of third trimester pregnant women with Hypnobirthing and further research needs to be done so that the results are more valid.